Bubbles and onis - Albers, Peter; Frauenfelder, Urs (Journal of fixed point theory and applications, 2017)
In this article, we study the gradient flow equation of a variant of the Rabinowitz action functional on very negative line bundles and relate it to periodic orbits on the base of this bundle. On very negative line bundles, there are generically no holomorphic spheres.
Puplished online: 03 November 2016
Gesehen am 14.08.2017